Susceptibilities of Haemophilus influenzae and Moraxella catarrhalis to ABT-773 Compared to Their Susceptibilities to 11 Other Agents - Credito, Kim L. (American Society for Microbiology, 2001)
The activity of the ketolide ABT-773 against Haemophilus and Moraxella was compared to those of 11 other agents. Against 210 Haemophilus influenzae strains (39.0% β-lactamase positive), microbroth dilution tests showed that azithromycin and ABT-773 had the lowest MICs (0.5 to 4.0 and 1.0 to 8.0 μg/ml, respectively), followed by clarithromycin and roxithromycin (4.0 to >32.0 μg/ml). Of the β-lactams, ceftriaxone had the lowest MICs (≤0.004 to 0.016 μg/ml), followed by cefixime and cefpodoxime (0.008 to 0.125 and ≤0.125 to 0.25 μg/ml, respectively), amoxicillin-clavulanate (0.125 to 4.0 μg/ml), and cefuroxime (0.25 to 8.0 μg/ml). Amoxicillin was only active against β-lactamase-negative strains, and cefprozil had the highest MICs of all oral cephalosporins tested (0.5 to >32.0 μg/ml). Against 50 Moraxella catarrhalis strains, all of the compounds except amoxicillin and cefprozil were active. Time-kill studies against 10 H. influenzae strains showed that ABT-773, at two times the MIC, was bactericidal against 9 of 10 strains, with 99% killing of all strains at the MIC after 24 h; at 12 h, ABT-773 gave 90% killing of all strains at two times the MIC. At 3 and 6 h, killing by ABT-773 was slower, with 99.9% killing of four strains at two times the MIC after 6 h. Similar results were found for azithromycin, with slightly slower killing by erythromycin, clarithromycin, and roxithromycin, especially at earlier times. β-Lactams were bactericidal against 8 to 10 strains at two times the MIC after 24 h, with slower killing at earlier time periods. Most compounds gave good killing of five M. catarrhalis strains, with β-lactams killing more rapidly than other drugs. ABT-773 and azithromycin gave the longest postantibiotic effects (PAEs) of the ketolide-macrolide-azalide group tested (4.4 to >8.0 h), followed by clarithromycin, erythromycin, and roxithromycin. β-Lactam PAEs were similar and shorter than those of the ketolide-macrolide-azalide group for all strains tested.